Análise da influência da amplitude de vibração no ensaio de cavitação de um aço inox 304 - Goes, Wellington Uczak de (2014)
The advancement in the creation of most resistant materials leads to the further study of the phenomena which the materials are exposed to, in this context the work was formulated. This course conclusion work objetive was to perform an experimental investigation of the variation of the vibration amplitude in a 304 stainless steel, and this issue is related to the tribological process of cavitation. The experimental investigation was performed in the laboratory of Materials in the Federal Technological University of Paraná campus Ponta Grossa, using equipment ultrasonic cavitation through the vibratory method attending to ASTM G32/03 modified for the indirect method. The next part of the work was the characterization of the specimens also performed in the Materials Laboratory, first by the use of the Shimadzu analytical balance AW220 for evaluation of the weight loss, then these data they were compared with those available in the literature, after the data conferred was used the 3D optical profilometer from the brand Taylor Hobson CCI Lite to observe the surface roughness and profile of the worn surface. With the appropriate results established in the previous phase, started the next phase where several tables and comparative charts were created, between the different amplitudes of 40%, 60%, 70% and 80% of 60 μm along the testing time and when was possible these results were compared with existing literature on the subject in regards to graphics and tables generated and always presenting a concordance of the data.